Serverless Web Application for The Life Cycle of Software Development Projects using Scrum in South America - Busto, Pablo Josue Francia Del (2023)
Serverless models are one of the latest architecture models provided by Cloud vendors such as AWS and Microsoft; we are exploring serverless applications to develop a progressive web application that will help future developers and project leaders to manage their projects better by having a tool that will help incorporate Scrum properly into their projects. As seen in the investigation done, we can see that South America is below the global average in completing projects on time or within the planned budget. In this work we explain the agile life cycle of the web application developed, focusing on the Scrum aspects of the tool design, the serverless architecture of the app and its following development, while also applying an analysis of the current projects to measure the level of effectiveness that a proper Scrum method can have on finishing a project correctly on time. With our initial surveys landing a score of 80 in the positive version of the System Usability Scale and getting good results in the completion of our main quality metrics, we can see that there is indeed an interest in finding a tool that helps use Scrum properly by adding video calls as a mean of direct communication between users.